ECOLOGICAL TOURISM FEATURES AND PERSPECTIVES IN THE URAL AND IN THE PERM KRAI (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The article provides the current concepts of ecological, self-regulatory, active and sport tourism in Russia, highlights the present state of ecological tourism, and deals with its rational spatial organization in the Ural territory and Perm Krai.
Keywords: ecological; active; sport; self-regulatory tourism; territorial organization; Perm; Ural Mountains